2002
DOI: 10.1515/cclm.2002.171
|View full text |Cite
|
Sign up to set email alerts
|

Gene Polymorphism and Coronary Risk Factors in Indian Population

Abstract: Asian Indians who have settled overseas and those in urban India have increased risk of coronary events. Reasons for this increased risk are thought to be genetic but are yet unclear. Advances in molecular cardiology have revealed a number of single nucleotide polymorphisms associated with atherosclerosis. In this review, gene polymorphisms that have been associated with coronary diseases among Indians are discussed. Topics include the genes involved in hyperlipidemia, hypertension, and homocysteine. Mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 79 publications
1
21
0
Order By: Relevance
“…It can increase triglycerides by inhibiting lipases (26). Insulin reduces apoC3 expression and induces HL expression (14,27) to help remove postprandial triglycerides (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can increase triglycerides by inhibiting lipases (26). Insulin reduces apoC3 expression and induces HL expression (14,27) to help remove postprandial triglycerides (26).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin reduces apoC3 expression and induces HL expression (14,27) to help remove postprandial triglycerides (26). The Ϫ482C3 T polymorphism lies in an apoC3 gene promoter insulin response element, and functional studies have demonstrated that the Ϫ482T allele reduces the inhibitory effect of insulin on apoC3 expression (26).…”
Section: Discussionmentioning
confidence: 99%
“…At the MS gene, an A to G transition at nucleotide 2756 (A2756G), which results in the substitution of glycine for aspartic acid at amino acid position 919 (D919G), has been described [4]. In Indian [5] and Korean [6] populations, the 2756G allele was found to be associated with increased Hcy levels. Finally at the MTHFR gene, a common C to T transition at nucleotide 677 (C677T), which leads to the substitution of valine for alanine, has been reported to impair the enzymatic activity of MTHFR [7], and the homozygous form of the 677T allele (T/T genotype) is therefore associated with higher Hcy concentrations than the other two genotypes among major Asian populations including Japanese [8,9], Koreans [6], and Chinese [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that genetic variation is important for the pathogenesis of coronary artery disease (CAD), myocardial infarction (MI) and clinical outcome (1,2). Although numerous candidate genes have been implicated in the development and progression of atherosclerosis, the genes that are responsible remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%